Pengaruh Penggunaan Chat GPT Terhadap Literasi Matematika Mahasiswa Pendidikan Matematika Universitas Dayanu Ikhsanuddin - Devianti Devianti; La Eru Ugi; Rismayani Armin (Jurnal Akademik Pendidikan Matematika, 2026)
The problem in this study is, Is there any significant effect of GPT Chat usage on mathematical literacy of Mathematics Education students at Dayanu Ikhsanuddin University? This study aims to determine the effect of GPT Chat usage on mathematical literacy of Mathematics Education students at Dayanu Ikhsanuddin University. This study used quantitative research by applying a correlational method. The population was all active students in the odd semester of the 2024/2025 academic year of Mathematics Education at Dayanu Ikhsanuddin University, totaling 98 students. The sample in this study was all fourth semester Mathematics Education students at Dayanu Ikhsanuddin University, totaling 22 students. The research instrument used a questionnaire, and data analysis techniques used descriptive statistical analysis and inferential statistical analysis. The results of this study are (1) normality and linearity tests, which indicate that the data are normally and linearly distributed. (2) hypothesis testing using simple linear regression analysis. The significance value obtained was 0.002 with t count = 3.534 > t table 2.086. Because the significance value is 0.002<0.05, HO is rejected and HI is accepted based on the hypothesis acceptance criteria. Therefore, it can be concluded that there is a significant effect of GPT Chat usage on the mathematical literacy of Mathematics Education students at Dayanu Ikhsanuddin University.